2018
DOI: 10.1111/iej.13034
|View full text |Cite
|
Sign up to set email alerts
|

Is a calcium hydroxide liner necessary in the treatment of deep caries lesions? A systematic review and meta‐analysis

Abstract: The aim of this systematic review and meta‐analysis was to evaluate whether the use of calcium hydroxide (CH) liner improves the clinical success in the treatment of deep caries lesions of primary and permanent teeth. The review was reported in accordance with the PRISMA Statement. Only studies that evaluated deep carious lesions treated with and without a CH liner were included. The required outcomes had to be obtained by clinical, radiographic or laboratory evaluations. Statistical analyses were performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
2
31
0
6
Order By: Relevance
“…While there was a general preference among respondents of the current study to place a liner, a recent systematic review has shown that the evidence is inconsistent in terms of postoperative sensitivity with use of liners under resin‐bonded restorations . Another recent systematic review on whether calcium hydroxide liner is required for deep caries lesions confirmed these findings that treatment of the deep caries lesion is not a material‐dependant technique . This is also in line with the latest consensus recommendations which stated that there is no evidence to recommend a specific material .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While there was a general preference among respondents of the current study to place a liner, a recent systematic review has shown that the evidence is inconsistent in terms of postoperative sensitivity with use of liners under resin‐bonded restorations . Another recent systematic review on whether calcium hydroxide liner is required for deep caries lesions confirmed these findings that treatment of the deep caries lesion is not a material‐dependant technique . This is also in line with the latest consensus recommendations which stated that there is no evidence to recommend a specific material .…”
Section: Discussionsupporting
confidence: 78%
“…13 Another recent systematic review on whether calcium hydroxide liner is required for deep caries lesions confirmed these findings that treatment of the deep caries lesion is not a material-dependant technique. 30 This is also in line with the latest consensus recommendations which stated that there is no evidence to recommend a specific material. 5 The great variance in the type of lining materials chosen by Australian dentists suggests the need to disseminate the current thinking in this space to the wider audience.…”
Section: Discussionsupporting
confidence: 74%
“…Há um consenso de que o principal objetivo do hidróxido de cálcio é provocar a remineralização e, consequentemente, proteção da polpa 33,37,39 . Contudo, dentes tratados com cimento de ionômero de vidro modificado por resina (CIV-MR) ou com hidróxido de cálcio resultaram em uma espessura de dentina reparativa similar 9,40 .…”
Section: Discussionunclassified
“…Rosa et al 37 constataram que existem poucos indícios para apoiar o uso de hidróxido de cálcio como agente forrador. Na dentição decídua, o nível de indicação foi equilibrado ao ser comparado com o CIV-MR, e baixo quando comparado com materiais inertes ou sistemas adesivos.…”
Section: Discussionunclassified
See 1 more Smart Citation